CLINICAL OUTCOME OF INTERSPHINCTERIC RESECTION FOR ULTRA-LOW RECTAL CANCER - Valentin L. Ignatov; Nikola Y. Kolev; Anton Y. Tonev; Georgi H. Ivanov; Aleksander K. Zlatarov; Georgi Todorov; Velian Platikanov; Krasimir D. Ivanov (Peytchinski Publishing, 2012)
BACKGROUND: Laparoscopic surgery has been reported to be one of the approaches for total mesorectal excision (TME) in rectal cancer surgery. Intersphincteric resection (ISR) has been reported as a promising method for sphincter-preserving operation in selected patients with very low rectal cancer. METHODS: We try to underline the important surgical issues surrounding the management of patients with low rectal cancer indicated to laparoscopic intersphincteric resection (ISR). From January 2007 till now, 35 patients with very low rectal cancer underwent laparoscopic TME with ISR. We report and analyze the results from them RESULTS: Conversion to open surgery was necessary in one (3%) patient. The median operation time was 293 min and median estimated blood loss was 40 ml. The pelvic plexus was completely preserved in 32 patients. There was no mortality. Postoperative complications occurred in three (9%) patients. The median length of postoperative hospital stay was 11 days. Macroscopic complete mesorectal excision was achieved in all cases. Complete resection (R0) was achieved in 21 (91%) patients.CONCLUSIONS: Laparoscopic TME with ISR is technically feasible and a safe alternative to laparotomy with favorable short-term postoperative outcomes. The literature research made by us found that the laparoscopic approach can be underwent in most patients with low rectal cancer in which laparoscopic ISR represents a feasible alternative to conventional open surgery.